Pesquisas mineralógicas e geoquímicas para a distinção de basaltos intrusivos e extrusivos no Vogelsberg Alemanha Federal - OLIVEIRA, Elson Paiva de (Universidade Federal do Pará, 2017)
In a drill hole of 450m made in the central part of the volcanic complex Vogelsberg, West Germany many authors found an alternating sequence of alkali olivinbasalts and tholeiites, consisting of 7 series with a total of 293m. Radiometric age dating suggests that two of the alkali olivinbasalts are intrusive. One of them, serie 3, however shows traces of weathering on its surface. The present study includes chemical analyses of major and trace elements (Ni, Co, Cu, Zn, Li and Be) as well as mineralogical investigation by means of X-ray diffraction and optial methods. The objective of these analyses was the chemical and mineralogical characterization of the weathering horizons and of the possible effects of differentiation in the units considered intrusive. The commom association of haematite, montmorillonite and quartz fragments in the weathered horizons, as well as the increase of Ni, Co, Cu, H2O and Fe2O3 and the decrease of Li, Be, FeO, MgO and CaO from the bottom to the top of one of the "intrusive units" in serie 3, shows that this unit was exposed to the earth's surface and therefore cannot be considered intrusive. The other alkali olivinbasalt in serie 5 shows incipient gravitative differentiation effects but witho ut significant textural variations. On the other hand there is amigdaloidal texture on its top suggesting also an extrusive nature.